Acute Respiratory Distress Syndrome: Cost (Early and Long-Term) - Bice, Thomas; Carson, Shannon S. (Seminars in Respiratory and Critical Care Medicine, 2019)
Costs of care in the intensive care unit are a frequent area of concern in our current health care system. Utilization of critical care services in the United States, particularly near the end of life, has been steadily increasing and will continue to do so. Acute respiratory distress syndrome (ARDS) is a common and important complication of critical illness. Patients with ARDS frequently experience prolonged hospitalizations and consume significant health care resources. Many patients are discharged with functional limitations and require significant postdischarge services. These patients have a high susceptibility to new complications which require significant additional health care resources. There is a slowly growing literature on the cost-effectiveness of the treatment of ARDS; despite its high costs, treatment remains a cost-effective intervention by most societal standards. However, when ARDS leads to prolonged mechanical ventilation, treatment may become less cost-effective. In addition, the provision of extracorporeal life support adds another layer of complexity to these cases. Small reductions in intensive care unit length of stay may benefit patients, but they do not lead to significant reductions in overall hospital costs. Early discharge to postacute care facilities can reduce hospital costs but is unlikely to significantly decrease costs for an entire episode of illness. Improved effectiveness of communication between clinicians and patients or their surrogates could help avoid costly interventions with poor expected outcomes. However, the most significant cost-saving interventions are early recognition and treatment of conditions to potentially prevent the development of this serious complication.
Keywords: ARDS; mechanical ventilation; ECMO; critical care; costs